Mentoring Preparation of KPIs to Strengthen the Managerial Capacity of PKU Sekapuk Hospital Staff - Tjatur Ermitajani Judi (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2025)
The limited managerial competency of 80% of the Human Resources (HR) staff with clinical backgrounds at PKU Sekapuk Hospital, Lamongan, has resulted in poor performance appraisal standards. Daily internal evaluations, relying on spot inspections, have been shown to trigger highly subjective bias, role ambiguity, and a culture of fear that hinders innovation in healthcare services. This Community Empowerment Program (CEP) aims to strengthen managerial capacity and staff accountability through a paradigm shift from a reactive spot inspection model to a transparent, written target system. The methods implemented include participatory workshops, self-design assistance, and assessment instrument simulations with 25 core management elements and ward heads. The program results demonstrated a highly cooperative organizational psychological response. Management and leaders welcomed the elimination of the conventional spot inspection system. This activity succeeded in drafting written Key Performance Indicators (KPIs) regulations based on the S.M.A.R.T (Specific, Measurable, Achievable, Relevant, Time-bound) principles, covering the pillars of clinical quality, operational efficiency, and financial compliance. Effective KPIs implementation cuts through cross-unit sectoral egos, provides role clarity, and builds a work culture that is aware of performance data.